You are on page 1of 11

# Worksheet 4.

7 Polynomials

## Section 1 Introduction to Polynomials

A polynomial is an expression of the form p(x) = p0 + p1 x + p2 x2 + + pn xn where p0 , p1 , . . . , pn are constants and x is a variable. Example 1 : f (x) = 3 + 5x + 7x2 x4 Example 2 : g (x) = 2x3 + 3x (p0 = 3, p1 = 5, p2 = 7, p3 = 0, p4 = 1) (n N)

(p0 = 0, p1 = 3, p2 = 0, p3 = 2)

The constants p0 , . . . , pn are called coecients. In Example 1 the coecient of x is 5 and the coecient of x4 is 1. The term which is independent of x is called the constant term. In Example 1 the constant term of f (x) is 3; in Example 2 the constant term of g (x) is 0. A polynomial p0 + p1 x + + pn xn is said to have degree n, denoted deg n, if pn = 0 and xn is the highest power of x which appears. In Example 1 the degree of f (x) is 4; in Example 2 the degree of g (x) is 3. A zero polynomial is a polynomial whose coecients are all 0 i.e. p0 = p1 = = pn = 0. Two polynomials are equal if all the coecients of the corresponding powers of x are equal.

Exercises: 1. Find (i) the constant term, (ii) the coecient of x4 and (iii) the degree of the following polynomials. (a) x4 + x3 + x2 + x + 1 (b) 9 3x2 + 7x3 (d) 10x5 3x4 + 5x + 6 1 (c) x 2

(e) 3x6 + 7x4 + 2x (f) 7 + 5x + x2 6x4 2. Suppose f (x) = 2ax3 3x2 b2 x 7 and g (x) = cx4 + 10x3 (d + 1)x2 4x + e. Find values for constants a, b, c, d and e given that f (x) = g (x).

## Section 2 Operation on Polynomials

Suppose h(x) = 3x2 + 4x + 5 k (x) = 7x2 3x

Addition/Subtraction: To add/subtract polynomials we combine like terms. Example 1 : We have h(x) + k (x) = 10x2 + x + 5 Multiplication: To multiply polynomials we expand and then simplify their product. Example 2 : We have h(x) k (x) = (3x2 + 4x + 5)(7x2 3x) = 21x4 9x3 + 28x3 12x2 + 35x2 15x = 21x4 + 19x3 + 23x2 15x Substitution: We can substitute in dierent values of x to nd the value of our polynomial at this point. Example 3 : We have h(1) = 3(1)2 + 4(1) + 5 = 12 k (2) = 7(2)2 3(2) = 34 Division: To divide one polynomial by another we use the method of long division. Example 4 : Suppose we wanted to divide 3x3 2x2 + 4x + 7 by x2 + 2x. x2 + 2x 3x 8 3x3 2x2 + 4x + 7 3x3 + 6x2 8x2 + 4x 8x2 16x 20x + 7 2

So 3x3 2x2 + 4x + 7 divided by x2 + 2x gives us a quotient of 3x 8 with a remainder of 20x + 7. We have 3x3 2x2 + 4x + 7 = (x2 + 2x)(3x 8) + (20x + 7). More formally, suppose p(x) and f (x) are polynomials where deg p(x) deg f (x). Then dividing p(x) by f (x) gives us the identity p(x) = f (x)q (x) + r (x), where q (x) is the quotient, r (x) is the remainder and deg r (x) < deg f (x). Example 5 : Dividing p(x) = x3 7x2 + 4 by f (x) = x 1 we obtain the following result: x2 6x 6 x 1 x3 7x2 + 0x + 4 x3 x 2 6x2 + 0x 6x2 + 6x 6x + 4 6x + 6 2 Here the quotient is q (x) = x2 6x 6 and the remainder is r = 2. Note: As we can see, division doesnt always produce a polynomial annswer- sometimes theres just a constant remainder.

Exercises: 1. Perform the following operations and nd the degree of the result. (a) (2x 4x2 + 7) + (3x2 12x 7) (c) (x2 + 2x + 1)2

## (b) (x2 + 3x)(4x3 3x 1)

(d) (5x4 7x3 + 2x + 1) (6x4 + 8x3 2x 3) 2. Let p(x) = 3x4 + 7x2 10x + 4. Find p(1), p(0) and p(2). 3. Carry out of the following divisions and write your answer in the form p(x) = f (x)q (x) + r (x). (a) (3x3 x2 + 4x + 7) (x + 2)

## (b) (3x3 x2 + 4x + 7) (x2 + 2) 3

(d) (5x4 + 30x3 6x2 + 8x) (x2 3x + 1) (e) (3x4 + x) (x2 + 4x) 4. Find the quotient and remainder of the following divisions. (a) (2x4 2x2 1) (2x3 x 1) (c) (5x4 3x2 + 2x + 1) (x2 2) (e) (x4 + 1) (x + 1)

## Section 3 Remainder Theorem

We have seein in Section 2 that if a polynomial p(x) is divided by polynomial f (x), where deg p(x) deg f (x), we obtain the expression p(x) = f (x)q (x) + r (x), where q (x) is the quotient, r (x) is the remainder and deg r (x) < deg f (x), or r = 0. Now suppose f (x) = x a, where a R, then i.e p(x) = (x a)q (x) + r (x) p(x) = (x a)q (x) + r , since deg r < deg f.

## If we let x = a then we get i.e. p(a) = (a a)q (a) + r p(a) = r.

So the remainder when p(x) is divided by x a is p(a). This important result is known as the remainder theorem Remainder Theorem: If a polynomial p(x) is divided by (x a), then the remainder is p(a). Example 1 : Find the remainder when x3 7x2 + 4 is divided by x 1.

Instead of going through the long division process to nd the remainder, we can now use the remainder theorem. The remainder when p(x) = x3 7x2 +4 is divided by x 1 is p(1) = (1)3 7(1)2 + 4 = 2. 4

Note: Checking this using long division will give the same remainder of 2 (see Example 5 from Section 2).

Exercises: 1. Using the remainder theorem nd the remainder of the following divisions and then check your answers by long divsion. (a) (4x3 x2 + 2x + 1) (x 5)

## Section 4 The Factor Theorem and Roots of Polynomials

The remainder theorem told us that if p(x) is divided by (x a) then the remainder is p(a). Notice theat the remainder p(a) = 0 then (x a) fully divides into p(x) i.e. (x a) is a factor of p(x). This is the factor theorem. Factor Theorem: Suppose p(x) is a polynomial and p(a) = 0. Then (x a) is a factor of p(x) and we can write p(x) = (x a)q (x) for some polynomial q (x). Note: If p(a) = 0 we call x = a a root of p(x). We can use trial and error to nd solutions of polynomial p(x) by nding a number a whre p(a) = 0. If we can nd such a number a then we know (x a) is a factor of p(x), and then we can use long division to nd the remaining factors of p(x). Example 1 : a) Find all the factors of p(x) = 6x3 17x2 + 11x 2. b) Hence nd all the solutions to 6x3 17x2 + 11x 2 = 0. 5

Solution a) By trial and error notice that p(2) = 48 66 + 22 2 = 0 i.e. 2 is a root of p(x). So x 2 is a factor of p(x). To nd other factors well divide p(x) by (x 2). x2 6x2 5x + 1 6x3 17x2 + 11x 2 6x3 12x2 5x2 + 11x 5x2 + 10x x2 x2 0

So p(x) = (x 2)(6x2 5x + 1). Now notice 6x2 5x + 1 = 6x2 3x 2x + 1 = 3x(2x 1) (2x 1) = (3x 1)(2x 1) Solution b) The solutions to p(x) = 0 occur when x 2 = 0, That is, x = 2, 3x 1 = 0, 1 x= , 3 So p(x) = (x 2)(3x 1)(2x 1) and its factors are (x 2), (3x 1) and (2x 1). 2x 1 = 0. 1 x= . 2

Exercises: 1. For each of the following polynomials nd (i) its factors; (ii) its roots. (a) x3 3x2 + 5x 6 (c) 6x3 x2 2x

(b) x3 + 3x2 9x + 5

(d) 4x3 7x2 14x 3 2. Given that x 2 is a factor of the polynomial x3 kx2 24x + 28, nd k and the roots of this polynomial. 6

1 3

## and whose value at x = 2 is 10.

4. Find the polynomial of degree 3 which has a root at 1, a double root at 3 and whose value at x = 2 is 12. 5. (a) Explain why the polynomial p(x) = 3x2 + 11x2 + 8x 4 has at least 1 root in the interval from x = 0 to x = 1. (b) Find all the roots of this polynomial.

## Exercises 4.7 Polynomials

1. Find the quotient and remainder of the following divisions. (a) (x3 x2 + 8x 5) (x2 7) (c) (2x3 6x2 x + 6) (x 6)

## (b) (x3 + 5x2 + 15) (x + 3)

(d) (x4 + 3x3 x2 2x 7) (x2 + 3x + 1) 2. Find the factors of the following polynomials. (a) 3x3 8x2 5x + 6 (c) 2x3 + 5x2 3x

(b) x3 4x2 + 6x 2

## 3. Solve the following equations. (a) x3 3x2 + x + 2 = 0

(b) 5x3 + 23x2 + 10x 8 = 0 (d) x3 2x2 + 5x 4 = 0 (c) x3 8x2 + 21x 18 = 0 (e) x3 + 5x2 4x + 20 = 0

4. Consider the polynomial p(x) = x3 4x2 + ax 3. (b) Find all the factors of p(x). (a) Find a if, when p(x) is divided by x + 1, the remainder is 12.

5. Consider the polynomial h(x) = 3x3 kx2 6x + 8. (b) Hence nd all the roots of h(x). (a) Given that x 4 is a factor of h(x), nd k and nd the other factors of h(x).
1 5

## and whose value at x = 0 is 3.

7. Find the quadratic which has a remainder of 6 when divided by x 1, a remainder of 4 when divided by x 3 and no remainder when divided by x + 1. 8. Find the polynomial of degree 3 which has roots at x = 1, x = 1 + 2 and x = 1 2, and whose value at x = 2 is 2.

Section 1 1. (a) (i) 1 (b) (i) 9 (c) (i) 2 (ii) 1 (ii) 0 (ii) 0 (iii) 4 (iii) 3 (iii) 1 (d) (i) 6 (e) (i) 0 (f) (i) 7 (ii) 3 (iii) 5 (iii) 6 (iii) 4

(ii) 7

(ii) 6

## (d) x4 15x3 + 6x + 4, 2. p(1) = 4, p(0) = 4,

deg = 4

p(2) = 100

3. (a) 3x3 x2 + 4x + 7 = (x + 2)(3x2 7x + 18) 29 (c) x4 3x2 + 2x + 4 = (x 1)(x3 + x2 2x) + 4 (e) 3x4 + x = (x2 + 4x)(3x2 12x + 48) 191x r (x) = x2 + x 1 r (x) = 3 r (x) = 2x + 15 r (x) = 75x + 60 r (x) = 2

(b) 3x3 x2 + 4x + 7 = (x2 + 2)(3x 1) + (2x + 9) (d) 5x4 + 30x3 6x2 + 8x = (x2 3x + 1)(5x2 + 45x + 64) + (155x 64)

4. (a) q (x) = x,

(b) q (x) = x + 3,

## (d) q (x) = x2 4x + 15,

(e) q (x) = x3 x2 + x 1,

2

## (c) x(2x + 1)(3x 2)

2. k = 3,

roots: 2 (double), 7

## 3. 6x2 + 4x 2 4. 4x3 20x2 + 12x + 36 5. (b) 1 , 2 3 Exercises 4.7 1. (a) q (x) = x 1,

2

r (x) = x + 2 r = 33

(b) q (x) = x 2x 6, (b) (x 2)(x2 2x + 2) (d) (x 1)(x2 + x 2) (e) (x + 2)3 (c) x(2x 1)(x + 3)

(d) q (x) = x 1,

r=0 r (x) = 4x 5

3. (a) 2, (b)
2 , 5

1+ 5 , 2

1 5 2

1, 4 2

2,

5. (a) k = 11,

2 3

11